Oxidative stress of glyphosate, AMPA and metabolites of pyrethroids and chlorpyrifos pesticides among primary school children in Cyprus - Makris, Konstantinos C.; Euthymiou, Nikolaos; Konstantinou, Corina; Anastasi, Elena; Schoeters, Greet; Kolossa-Gehring, Marike; Katsonouri, Andromachi (My University, 2022)
Exposure to various pesticides, such as pyrethroids and chlorpyrifos, has been previously associated with adverse effects on children's health. Scientific evidence on the human toxicity of glyphosate (GLY) and its primary metabolite, aminomethylphosphonic acid (AMPA) is limited, particularly for children. This study aimed to i) assess the exposure determinants of the studied pesticides measured in children in Cyprus, and ii) determine the association between the urinary pesticides and the biomarkers of DNA and lipid oxidative damage.
Keywords: AMPA; Children; Glyphosate; Human biomonitoring; Oxidative stress; Pesticides